The Effect of the Si Dia Video on the Duration of Labor in Pregnant Women in the Islands Community - Nurniati Tianastia Rullyni; Vina Jayanti; Rita Ridayani; Neny San Agustina (Health Notions, 2023)
WHO estimates that 10.7 million women are dying as a result of pregnancy. Around 25-50% are related to a persalinan problem. One factor that influences performance is personal psychology. Peran keluarga aktif dalam persalinan akan mengurangi kejadian komplikasi. The goal of this study is to determine the impact of video-based persalinan on long-term persalinan in the kepulauan population. The design of this study was posttest only with control group. The research carried out at Tanjungpinang's Mandiri Praktik Bidan in the months of March and May 2022, involved 68 maternity mothers. The method of investigation used was observation checklist. Data were analyzed using independent sample t-test. The results of the study show that there was a benefit to video-based persalinan compared to traditional labor. Keywords: labor companion video; length of labor